Kinetic architecture - Zuk, William; Clark, Roger H. (New York : Van Nostrand Reinhold Company, Inc., 1970)
This book is about an architecture responsive to the essential characteristics of our society - change.
Introduction -- Kinetic Geneses -- Architectural applications -- Implications.
Includes bibliographical references and index.
Keywords: ARCHITECTURAL DRAWINGS